2017
DOI: 10.1080/13854046.2017.1413208
|View full text |Cite
|
Sign up to set email alerts
|

Communication is key: the utility of a revised neuropsychological report format

Abstract: We suggest that adaptation to efficient, readable, and effective reports is possible within the practice of neuropsychology. Findings encourage replication in other settings. Through collaboration with key stakeholders, providers can identify their populations' and audience's unique needs and set report targets accordingly. To encourage that practice, we summarize our general process, provide a set of guidelines that can be adapted across multiple settings, and include an appended sample report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…This is a higher reading level than other clinical reports. One study reviewed >55,000 radiology reports from multiple specialties and found that the average reading level varied from a high school junior to college sophomore, while a review of 240 neuropsychiatric reports found average reading levels between a high school sophomore and college freshman (Baum et al, ; Trofimova, Vey, Safdar, Duszak, & Kadom, ). From this limited information, it may be concluded that genomics reports are more difficult to read.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a higher reading level than other clinical reports. One study reviewed >55,000 radiology reports from multiple specialties and found that the average reading level varied from a high school junior to college sophomore, while a review of 240 neuropsychiatric reports found average reading levels between a high school sophomore and college freshman (Baum et al, ; Trofimova, Vey, Safdar, Duszak, & Kadom, ). From this limited information, it may be concluded that genomics reports are more difficult to read.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to lower readability by removing or rewording unnecessarily complex writing (i.e., jargon) may improve provider (and patient) comprehension. However, it has been argued that reducing writing complexity can lead to vagueness, decrease accuracy, and other negative downstream effects when interpreting results (Baum et al, ). Thus, a balance between clarity and simplicity is key to improving readability while maintaining quality.…”
Section: Discussionmentioning
confidence: 99%
“…There was a strong consensus that it is important for psychologists to identify and recommend evidence-based and realistic supports and interventions for the individuals whom they assess (Baum et al, 2017; Cheung et al, 2014; Donders, 2010; Ostojic-Aitkens et al, 2021). There should be a manageable number of recommendations that are customized to the individual’s needs.…”
Section: Topics Where Consensus Was Achieved With Minimal Debatementioning
confidence: 99%
“…Understanding written reports and remembering neuropsychological feedback might be even more challenging for people with cognitive impairments or low literacy [18]. Adapting these reports is often necessary to make findings more understandable for patients and family [19].…”
Section: Introductionmentioning
confidence: 99%